Colorimetric Analysis of Piroxicam (Biological Sciences - PJSIR, 2007)
. A si mpl e and accurate spectrophotometric method is proposed for the anal ysis of pi rox icarn. A ye l lowi sh-green complex was formed between pi roxicam and copper su l phate pentahyd rate at room tem perature, wh ich was determi ned at 480 nm. A val id Bee-Lambert's  plot  over the ran ge of 2 to 1 2 µg/ml  and the calculated  molar absorpti vi ty  is 3.98 x I  03 1/ mol/cm . Ni ne (9) out of eleven (1 1 ) brand s tested passed the test with val ues rangi ng from 97 to 1 03%, wh i le the other two brands havi ng percentage val ues outside th e specified range fai led the test This colorimetric method was successfu l l y appl ied to the analys i s of bul k pharmaceutical s and pharmaceutical dosage preparations and the result s have been stati s tical l y anal yzed. The proposed method is preci se, simple, sensiti ve and fast, enabl ing the di rect determination of pi rox icam without previous extraction and use of expensi ve equ i pment and tox ic/ unaffordable reagents.